Publications Repository Based on OAI-PMH 2.0 Using Google App Engine - Hendra Hendra; Jimmy Jimmy (Universitas Ahmad Dahlan, 2014)
Online publication of scientific papers by the colleges aims to improve the dissemination and access by the public and the industry to the research result. OAI-PMH standard 2.0 is a protocol that allows the publication metadata exposed by a data provider can be harvested online by a service provider without any human intervention . A publication portal that is equipped with metadata exposure will increase the access and wider spread through the services provider. This study aims to developing a publications repository application completed with meta data exposure facility based on OAI-PMH 2.0 that running on Google App Engine. Google App Engine is a PaaS service provided by Google. Application development is done using SDLC approach, and using OOAD at the analysis and design phases. The purpose of the application is to publish scientific papers by lecturers at STMIK IBBI named Portal Garuda STMIK IBBI. Based on the results of testing using OAI-PMH Validator, BASE OAI-PMH Validator, and successful registration of portal Garuda STMIK IBBI in OpenArchive.org, OpenDOAR, and the ROAR, as well as the result rating reaching 95% by WebArchivability, it is believed that the application is complies with OAI-PMH standard 2.0 and the W3C standard. By implementation of the application will help higher education institutions meet the obligations of the scientific paper publication that can be accessed online as well as letter of Dikti number 2050/ET/2011.